2015
DOI: 10.1007/s13157-015-0695-6
|View full text |Cite
|
Sign up to set email alerts
|

Managed Habitats Increase Occupancy of Black Rails (Laterallus jamaicensis) and May Buffer Impacts from Sea Level Rise

Abstract: Global wetland degradation and loss are occurring at a rapid rate, and in the United States over 50 % of wetlands in the lower 48 states have been altered since European settlement. In some cases, wetlands that were historically transformed for agriculture are now managed as wetland habitat. We conducted occupancy surveys for black rails (Laterallus jamaicensis) in managed and unmanaged areas of coastal South Carolina. We modeled landscape and local variables potentially influencing black rail occupancy and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Our validation metrics demonstrate that our occupancy models had good predictive ability. Without accounting for imperfect detection in validation data, the predictive ability of our models was similar to those from previous studies that used spatial habitat variables (and an independent validation dataset) to predict occupancy of other rail species: black rail ( Laterallus jamaicensis , AUC = 0.70; Roach and Barrett ) and king rail ( Rallus elegans , AUC = 0.72; Pickens and King ). However, when accounting for imperfect detection in the validation data, our occupancy models had substantially higher predictive ability than models from these studies.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our validation metrics demonstrate that our occupancy models had good predictive ability. Without accounting for imperfect detection in validation data, the predictive ability of our models was similar to those from previous studies that used spatial habitat variables (and an independent validation dataset) to predict occupancy of other rail species: black rail ( Laterallus jamaicensis , AUC = 0.70; Roach and Barrett ) and king rail ( Rallus elegans , AUC = 0.72; Pickens and King ). However, when accounting for imperfect detection in the validation data, our occupancy models had substantially higher predictive ability than models from these studies.…”
Section: Discussionsupporting
confidence: 67%
“…, Rota et al. , Pickens and King , Comte and Grenouillet , Roach and Barrett ). However, the AUC values in these studies likely underestimated the true predictive ability of the occupancy models because some unknown proportion of unoccupied sites in the validation data were actually occupied.…”
Section: Discussionmentioning
confidence: 98%
“…Example analyses illustrated the assessment of changes to the occupied breeding area for black rails, and suggested their breeding range has contracted by more than 70% in the 21st century. Additional analyses with black rails also demonstrated how to pair predictive habitat models with predictions of sea level rise, and indicated that breeding habitat for this species in low-lying coastal areas is vulnerable to future changes (see also Roach & Barrett, 2015). Both of these results are particularly alarming for black rail conservation given the existing concerns over their status (Conway & Sulzman, 2007;Roach & Barrett, 2015) and the recent recommendation to list the eastern subspecies under the Endangered Species Act.…”
Section: Discussionmentioning
confidence: 96%
“…Additional analyses with black rails also demonstrated how to pair predictive habitat models with predictions of sea level rise, and indicated that breeding habitat for this species in low-lying coastal areas is vulnerable to future changes (see also Roach & Barrett, 2015). Both of these results are particularly alarming for black rail conservation given the existing concerns over their status (Conway & Sulzman, 2007;Roach & Barrett, 2015) and the recent recommendation to list the eastern subspecies under the Endangered Species Act. Yet, data-driven assessments of marsh bird distributions and range contractions over their entire breeding ranges were not previously possible, and thus our models provide the ability to quantitatively assess changes in status over time.…”
Section: Discussionmentioning
confidence: 96%
“…Endangered Species Act. Yet, little is known about the species' life history and demography, aside from habitat requirements, because it is so secretive (Conway & Sulzman, 2007;Eddleman et al, 1994;Richmond et al, 2010a;Roach & Barrett, 2015). Black rails are rarely seen and appear to be weak flyers; however, similar species of rails have traveled great distances to colonize oceanic islands (Ripley & Beehler, 1985;Taylor, 1998).…”
Section: Conservation Implicationsmentioning
confidence: 99%